The girls of August [compact disc, unabridged] - Siddons, Anne Rivers (Hachette Audio, 2014)
Every August, four women would gather together to spend a week at the beach, renting a new house each year. The ritual began when they were in their twenties and their husbands were in medical school, and became a mainstay of every summer thereafter. Their only criteria was oceanfront and isolation, their only desire to strengthen their far-flung friendships. They called themselves the Girls of August. But when one of the Girls dies tragically, the group slowly drifts apart.